Association of genetic polymorphism of guanosintriphosphate of cyclohydrolases and catechol-O-methyltransferase with the frequency of the appearance of chronic pain after surgery - B. E. Gаbovich; A. Veske; F. Dаi; Yu. A. Kolesnikov (Вестник анестезиологии и реаниматологии)
The objective of our clinical study was to identify the relationship between the incidence of persistent pain in the late postoperative period and polymorphisms (SNP) in the COMT and GCH1 genes.Subjects and methods. Following the provision of written informed consent, 102 patients (57 women and 45 men) with ASA physical condition I/II underwent transabdominal radical prostatectomy (n = 45) or hysterectomy (n = 57) for cancer-related pathology. The frequency and intensity of postoperative residual pain in the pelvic and scar areas were assessed by a nurse in all patients using a telephone survey three months after discharge from the clinic. Genotyping was performed in the region Chr14q22.1 and 22q11.21 containing the genes GCH1 and COMT, respectively. We identified five SNP GCH1s that, as shown, had a significant association with pain reactions in a previous study by Tegeder and co-authors: rs752688, rs4411417, rs8007201, rs3783641 and rs8007267, and one SNP COMT-rs4680 G1947A.Results and discussion. In the first three months after discharge from the hospital, 35 patients (34.3%) were diagnosed with moderate and severe pain of varying duration. In this group, 6 (17.1%) patients manifested signs of chronic neuropathic pain. Statistical analysis of 102 patients undergoing surgery on the lower floor of the abdominal cavity showed a statistically significant relationship only between GCH1 rs752688 and the more frequent occurrence of chronic postoperative pain. This relationship was mainly found in the male patient group, which indicated a gender-dependent effect. SNP GCH1rs752688 can be used as a clinical "marker" of chronic pain.